Extraction of a low grade zinc ore using gravity and froth flotation methods - Alabi Oladunni Oyelola; Dalhatu Aboki Abdu; Abere Dare Victor; Magnus T Igonwelundu; Bala Meshack Bosan; Araoye Babatunde Oyebode (Journal of Applied Sciences and Environmental Management)
Extraction of low grade zinc ore found in Gumau- Toro town was carried out using gravity and froth flotation methods. Analysis of the chemical composition reveals that the crude ore contains 20.20% Zinc and other related minerals such as  66.72% SiO2, 2.36%.Pb, 16.62%Fe, 0.001%Ag, these are impurities that  hindered the grade of zinc in this ore from appreciating. Fractional and grain sieve size results revealed that the liberation size of the ore is at -355+250μm assaying 32.41%Zn. At this liberation sieve size, the low grade zinc ore was subjected to four different beneficiation methods using five kilograms (5kg) each as charge into  Wilfley shaking Table, Humphrey spiral concentrator, Air floating Machine and one kilogram (1kg) for froth flotation. Resulting products (concentrate and tailing) from these processes were analyzed using instrumentation method. Percentage recovery of each applied process was calculated. This was used to ascertain that the use of froth flotation that gives 74.32%Zn at a recovery of 84.62% stands out the best method for zinc extraction towards value addition to the low grade crude zinc ore. ©JASEM